Pengembangan dan Validasi Media Pembelajaran Interaktif Berbasis Game Pixel Menggunakan Godot Engine pada Materi Bangun Datar Kelas IV SD - Dhimas Endra Kumara; Wendri Wiratsiwi; Sri Cacik (PT. Hasba Edukasi Mandiri, 2026)
This study aims to develop a pixel game-based interactive learning media using the Godot Engine for flat shape material in Grade IV Elementary School and to analyze its validity. The research and development method used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validity testing was conducted by three expert validators: a media expert, a language expert, and a material expert. Validity assessment used a percentage scoring technique with the criteria ≥81% = Very Feasible, 61–80% = Feasible, 41–60% = Fairly Feasible. The results showed that media validation obtained a score of 60/60 (100%, Very Feasible), language validation 48/50 (96%, Very Feasible), and material validation 52/55 (94.55%, Very Feasible). The media expert noted the media was well-designed and suggested adding a university logo, usage instructions, and a developer profile. The language expert declared the media usable without revision. The material expert recommended aligning learning objectives to the ABCD format, improving content interactivity, and adding a reference list inside the game. Overall, the pixel game-based learning media using the Godot Engine has been declared valid and feasible for use as an interactive learning medium for flat shape material in Grade IV Elementary School.